GROSS MOTOR SKILLS AND PHYSICAL ACTIVITY LEVEL: IS THERE ANY GENDER DIFFERENCES IN NINE YEARS OLD CHILDREN? - Aleksandra Aleksic Veljkovic; Nenad Stojiljkovic; Lucija Milcic (University of Debrecen, Institute of Sport Sciences, 2021)
Proper growth and development of young school children require mastering different skills, especially gross motor skills - basic locomotor and manipulative skills. It is essential to monitor the physical activity of nine-year-old children necessary for further proper development and healthy habits, which will continue into adulthood. This study aims to determine physical activity level, BMI, and gender differences in the performance of gross motor skills in children aged nine years (± six months). The study involved 40 participants (20 girls and 20 boys). Their body height, body weight, and body mass index were 140.46 ± 5.72 cm; 37.84 ± 8.21 cm; and 19.09 ± 3.56, respectively. All participants completed the Physical Activity Questionnaire for Children and performed the Test of Gross Motor Development, Second Edition (TGMD-2), and two sub-tests of BOT-2 (Speed and Agility and Upper-Limb Coordination). T-test for independent samples was used to compare groups according to physical activity level (physically active and inactive group) and explore interactions with gender and BMI, and gross motor skills variables. F-values, p-values, and partial eta squared (ɳ2) values were reported as MANOVA outcomes. The results showed a significant difference between physical activity level and locomotor skills but not in manipulative skills. Further research should focus on various exercise programs that contribute to developing skills and participation in organized physical activity of children of different ages.